Teachers' Ability to Motivate Students in Based Learning High Order Thinking Skill - Mujakir, Mujakir; Harahap, Roudotun Hasanah; Maisarah, Anisa (Lembaga Penelitian dan Pendidikan Mandala, 2025)
The purpose of this study was to see students’ understanding of HOTS-based learning through the motivational abilities provided by the teacher. The method used is the descriptive quantitative method. The subjects of this study were teachers of MAN 4 Aceh Besar and students of class XI MIA-1. Data was collected by distributing questionnaires to teachers and class XI MIA-1 students at MAN 4 Aceh Besar as respondents. The research results yielded an average percentage of 62.5% of teachers strongly agree that motivating students in High Order Thinking Skill (HOTS) learning can be the domain of students understanding HOTS-based learning through the motivation given by the teacher. Then, students get an average percentage of 81.25% of students agree that the motivation given by the teacher can increase student motivation in HOTS-based learning